Vocal fold granulomas in six brachycephalic dogs: clinical, macroscopical and histological features. (5th June 2018) - Sarran, D.; Caron, A.; Billet, J. P.
Abstract : Vocal cord granulomas are rarely observed in brachycephalic breeds but often reported in humans as contact granulomas. Six French bulldogs were included in this retrospective descriptive study. Endoscopic laryngeal examinations were performed on all dogs under general anaesthesia. Vocal cord lesions were exclusively unilateral, exophytic, approximately 3‐mm wide ulcerated mucosal nodules, arising from the vocal cord. Histopathological examination mainly revealed chronic inflammatory changes on the laryngeal epithelium which were consistent with laryngeal granulomas described in humans, except for the location: vocal cord in dogs versus vocal process in humans. In humans, granulomas result from chronic physical or chemical insult to laryngeal mucosa (chronic cough or throat clearing, vocal abuse, gastro‐esophageal reflux). In brachycephalic breeds, chronic inspiratory efforts and air turbulences and gastro‐esophageal reflux are suspected to result in chronic laryngeal inflammation.